Identification and characterization of a SARS-CoV-2 specific CD8+ T cell response with immunodominant features - Anastasia Gangaev (Nature Portfolio, 2021)
Many viral antigens have been identified in patients with COVID-19 patients, but which of these result in meaningful immune responses is unclear. Here the authors identify a range of SARS-CoV-2 CD8+ T cell responses across patients including a response targeting an epitope of ORF1ab with immunodominant properties.